Association Between Size Of Residual Non-Functioning Pituitary Adenoma and Regrowth after Surgery - Praphanuwat, Todsapon; Suwansirikul, Songkiet; Vaniyapong, Tanat (Thai Journal of Neurological Surgery, 2025)
Objective: A residual non-functioning pituitary adenoma (NFPA) after surgical removal is a well-known predictive risk factor for the regrowth of tumors, but there is no guide for the size of the residual tumor to predict. This study utilized the size of the residual tumor to predict the regrowth of non-functioning pituitary adenoma after surgical removal and investigated other predictors for tumor regrowth. Methods: The retrospective study included 123 newly diagnosed NFPA cases that had been operated on at Maharaj Nakorn Chiang Mai Hospital from January 2009 to December 2020. The size of the residual tumor was monitored through CT scans or 1.5 Tesla MRI interpreted by a neurosurgeon and neuroradiologists. Multivariate analysis was employed to identify predictors of tumor regrowth, and the Kaplan-Meir method was used to determine regrowth-free survival. Results: This study comprised 123 patients newly diagnosed with NFPA after surgical removal. Comparisons were made between a regrowth/recurrence tumor group (22 patients) and a no-progression group (101 patients). Univariate analysis indicated that residual tumor size, especially tumors larger than 1 cm (HR 4.00, 95%CI 1.16-13.83, p = 0.03), was the most significant factor. In multivariate analysis, adjusted for radiotherapy, hormonal deficit, age, and gender, it was revealed that regrowth or recurrence of the tumor depends on the size, especially more than 1 cm (HR 6.52, 95%CI 1.37-31.07, p = 0.02). Conclusion: Residual non-functioning pituitary adenoma after surgical removal could predict progression in the future, particularly for sizes larger than 1 cm. Neurosurgeons must pay attention to patients in this group.